Emotional Maturity in Building Household Harmony from the Perspective of Maqashid Syariah: A Study of Married Couples in Samarinda City - Hidayat, Muhammad Yususf; Andaryuni, Lilik (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2023)
Harmony within a marital relationship reflects an ideal state where couples strive for balance and alignment across various aspects of their shared life. Emotional management stands as a cornerstone in achieving this harmony. This article delves into emotional maturity among couples in Samarinda City in building marital harmony from the perspective of Maqashid Sharia. The research method employed is qualitative with a case study approach, drawing data from interviews with married couples in Samarinda. Data analysis is conducted interactively, encompassing data collection, condensation, presentation, and conclusion drawing. The research findings assert that emotional maturity plays a pivotal role in achieving marital harmony. For couples in Samarinda, emotional maturity influences communication, conflict management, emotional involvement, and resilience in facing challenges. Integration with the principles of Maqashid Sharia also demonstrates the influence of Islamic values in supporting emotional maturity and affecting all aspects of family life.